A multilevel analysis of individual and school level influence on job stress among secondary school teachers in Kelantan, Malaysia - Rasudin, Nur Syahmina (2016)
Stress is known as a worldwide psychological problem. Stress that relates to the workplace is known as job stress. The teaching profession has been identified as one of the most stressful professions. Thus, the objectives of this study are to validate the instruments of Career Commitment Questionnaire (CCQ), Job Satisfaction Questionnaire (JSQ), School Level Environment Questionnaire (SLEQ) and Job Stress Level Inventory (JSLI) using Structural Equation Modeling (SEM), to determine the prevalence of job stress among secondary school teachers in Kota Bharu, Kelantan and to identify the most significant predictors at the individual level and school level on teachers’ job stress among secondary school teachers in Kota Bharu, Kelantan. One thousand questionnaires were distributed to respondents from 30 secondary schools in the Kota Bharu district by using multistage stratified cluster sampling in this cross-sectional study design. Individual level variables consisted of sociodemographic factors, the history of chronic diseases which were high blood pressure, asthma and diabetes, teachers’ career commitment and the teachers’ job satisfaction. School-level variables consisted of type of school location, school size and teachers’ perception of their school environment. Validation study shows that CCQ, JSQ, SLEQ and JSLI were validated instruments. All questionnaire had fulfilled the model fitness requirements with CCQ (Chi-square:1.631, RMSEA: 0.078, CFI: 0.971 and TLI: 0.967), JSQ (Chi-square: 1.20; RMSEA:0.045; CFI:0.996; TLI:0.988), SLEQ (Chi-square:1.417; RMSEA:0.063; CFI: 0.973; TLI:0.965) and JSLI (Chi-square: 1.488, RMSEA: 0.069, CFI: 0.944 and TLI: 0.934). All questionnaires also had good reliability with Cronbach alpha value greater than 0.70. The overall response rates is 89%. The job stress prevalence of secondary school teachers in Kota Bharu District is 45%. Final model of multilevel analysis shows that age, monthly income, gender, marital status, teachers who had high blood pressure, teachers’ career commitment and the teacher’s job satisfaction had a significant influence on teacher’s job stress at the individual level while type of school location becomes the only significant predictor at school level variables that predict teachers’ job stress among secondary school teachers in Kota Bharu, Kelantan. To recapitulate, this study shows the importance of using multilevel analysis to analyze nested data and shows that school characteristics also had influences on teachers’ job stress. Thus, this model is expected to make a significant contribution to the literature of teachers’ job stress in using advanced statistical analysis to analyze the data and contribute in identifying the significant predictors of teachers’ job stress at individual and school-level among secondary school teachers.